Coordinating Global Health Policy Responses - Bindenagel Šehović, Annamarie. author. aut Link
XV, 182 p. 1 illus. in color.
Keywords: This book identifies the main challenges to confronting global health (in)securities at three levels. First, at the level of zoonosis, to which HIV and Ebola, as well as H1Nn, MERS-CoV, and SARS belong, and which promise to continue to emerge. Second, at the level of the spread of these across bio-, ecological and political boundaries and borders, particularly nationally. These present challenges not only in terms of immunities, but also in terms of rights – who is eligible for treatment under whose responsibility? Finally, at the international level of global administration, presenting a challenge in terms of coordinated public health, legal, political, and economic response. The book develops coordinated policy recommendations for meeting these challenges in a globalized world, and examines the unique opportunities and challenges associated with the co-administration of the good of public health by both nation states and non-state actors. This book will be valuable read for studentsof Public Policy, Health Policy and Management, International Relations and Global Governance.